Additive Manufacturing of Intertwined Electrode Pairs ‐ Guided Mass Transport with Gyroids. Issue 1 (28th October 2022) - Wiesner, Florian; Limper, Alexander; Marth, Cedric; Brodersen, Anselm; Wessling, Matthias; Linkhorst, John
Abstract : Electrochemical flow reactors facilitate the storage of renewable energies and the carbon‐neutral production of platform chemicals. To maximize the reactor efficiency, unhindered mass transport in the flow channel and high surface electrodes is required. However, state‐of‐the‐art reactors are limited by the conventional parallel plate designs. Herein, 3D intertwined electrode pairs are presented, based on triply periodic minimal surfaces that facilitate mass transport and provide high surface areas. Three gyroid designs with outer dimensions of 20 × 40 × 70 mm are manufactured from stainless steel via selective laser melting and implemented into a conventional flow cell. By design, the electrodes are rendered porous through the targeted control of the energy density during fabrication. Mass transport characterization by use of the fast ferri‐/ferrocyanide redox reaction demonstrates that smaller unit cells and thus shorter interelectrode distances achieve significantly increased current densities. Moreover, the addition of convective channels formed by second‐level gyroid structures removes diffusion boundary layers by promoting convective flow in electrode vicinity. The convective flow enhancement of the microscale channels even surpasses the effect of the unit cell size reduction, demonstrating importance of mass transport control. The integrated electrode design holds great potential for efficient next‐generation electrochemical flow reactors. Abstract : Thanks to the high freedom of design in additive manufacturing, intertwined electrode pairs are designed. Compared to conventional parallel plate designs, the intertwined arrangement provides high surface‐to‐volume ratios of up to 10.1 cm 2  cm −3 and a constant interelectrode distance, which results in a highly homogeneous electric field. Gyroid convective channels are integrated into the structure to further enhance convective transport.